FACTORS ASSOCIATED WITH SYMPTOMS OF GASTROESOPHAGEAL REFLUX DISEASE AMONG MEDICAL STUDENTS OF UNIVERSITAS NEGERI GORONTALO - Andi Nurmala Putri Arkani; Laksmyn Kadir; Ayu Rofia Nurfadillah (PT. Jurnal Center Indonesia Publisher, 2026)
Disgestion is a very important process for the health and well-being of the body, if it s not properly managed, it can increase the risk of more serious health problems, one of which is Gastroesophageal Reflux Disease (GERD). Risk factors that may contribute to the development of GERD include poor dietary pattern, physical activity, medication use, sleep quality, lifestyle, and academic stress. This study employs an analytical and approach using a quantitative method with a cross-sectional design. The population and sample consisted of 106 students selected using purposive sampling. Data analysis was conducted using a univariate and bivariate analyses. The chi-square test result showed that dietary pattern, physical activity, medication use, sleep quality, lifestyle, and academic stress had a significant association with GERD symptoms, with p-values < 0,05. It is recommended that students pay attention to dietary patterns, physical activity, medication use, sleep quality, lifestyle, and manage stress properly to achieve better health. For the Faculty of Medicine, it is recommended that education be provided regarding the importance of maintaining stundent health, particularly in relation to dietary patterns, physical activity, medication use, sleep quality, lifestyle, and stress management. Future researchers are encouraged to further develop follow-up studies on factors associated with GERD symptoms.